Exploring the Potential of Quantum Computing for Drug Design - Fadhil Asyraq Rahim, Muhammad; Madya, Fatmawaty; M. Lisal, Lenny; Nur Asni, St. (Journal of Neonatal Surgery, 2025)
Background : The use of intrauterine devices (IUDs) is associated with several side effects, the most common of which include alterations in the menstrual cycle, dysmenorrhea, and device expulsion. However, comparative data on these outcomes based on mode of delivery vaginal versus cesarean section remain limited in Indonesia. This study aimed to compare clinical outcomes following postplacental IUD insertion in patients who underwent vaginal delivery versus cesarean section. Methods : This analytical observational study employed a prospective cohort design. The sample included 184 IUD acceptors recruited from Wahidin Sudirohusodo Hospital, Sitti Khadijah 1 Hospital, Syekh Yusuf Gowa Hospital, Fatimah Hospital, and Lapalaloi Hospital Maros. Participants were equally divided into two groups based on delivery method: vaginal delivery (n = 92) and cesarean section (n = 92). Outcome measures included changes in menstrual cycle characteristics, dysmenorrhea, abnormal vaginal discharge, IUD expulsion, continuation rates, and hematological parameters. Statistical analysis was performed using the Chi-square and Wilcoxon tests, with significance set at P < 0.05. Results : There were no statistically significant differences between the vaginal and cesarean delivery groups in terms of menstrual cycle length, number of pads used per day, duration of menstruation, menstrual pain, non-menstrual pelvic pain, abnormal vaginal discharge, spontaneous IUD expulsion, desire to continue IUD use, or hematological parameters at both 6 and 12 months post-insertion (P > 0.05).